Fatigue Study of Six and Eight mm Diameter Interlocking Nails with Screw Holes of Variable Size and Number - Dueland, R. T.; Vanderby, R., Jr; McCabe, R. P. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Clinical fatigue failure of 6 mm diameter interlocked nails (ILN) with holes accommodating 3.5 mm screws has been reported. This problem was investigated by testing eight different designs of 6 mm and 8 mm diameter ILN with a 2 plus 2 screw hole pattern and a multiple holed pattern. Interlocking nails with holes to accommodate 3.5 and 4.5 mm screws in 8 mm ILN and 2.7 and 3.5 mm screws in 6 mm diameter ILN were used. A rotating beam testing device produced uniform bending moments across a test region of the ILN containing at least two holes. These moments fully reversed with each cycle. Fatigue failure occurred through screw holes. Using statistical modeling, reduction of the 6 mm ILN hole size from accommodating 3.5 screws to 2.7 mm screws increased the estimated fatigue life (EFL) of the latter by 52 times, comparable to the EFL of the 8 mm ILN with 4.5 screw holes. Reducing the 8 mm ILN screw hole size from accommodating 4.5 screws to 3.5 mm screws increased the comparative EFL by eight times. Fatigue testing is a good method to compare fatigue behavior of various implant designs. This gives a surgeon more information when selecting an ILN for fracture fixation.Occasional breakage of interlocking nails (ILN) in clinical cases prompted fatigue testing of original ILN and new designs of ILN. This study documented base line fatigue resistance information of the various ILN designs. Results indicated smaller screw holes markedly increased the fatigue resistance of both 6 mm and 8 mm diameter ILN. This information will aid the surgeon in planning fracture treatment.
Keywords: Interlocking nail; fatigue failure; fatigue testing; fracture repair